The SiO2 on the surface of BaFe12O19 to prepare flexible films with excellent microwave absorption properties - Jie Liu; Zijing Dong; Zhaohuan Zhang; Runjun Sun; Min Chen; Hao Wang; Zhenhao Zhang; Mimi Zhang; Xiaoya Jia; Chao Zhi (Journal of Materials Research and Technology, 2022)
In order to obtain excellent microwave absorbing materials. BaFe12O19 powders were first prepared by microwave hydrothermal method in this study, and BaFe12O19@SiO2 core–shell structure composite powders with different contents of TEOS were prepared by the improved Stöber method. The morphology and magnetic properties were investigated. PVDF was used as film forming agent, flexible film was prepared by tape casting. The performance was shown that the BaFe12O19@SiO2 microwave absorbing film has a good absorbing performance in the 8–18 GHz band. When the matching thickness is 2.5 mm, the RLmin is −30.3 dB at 15.2 GHz, and the effective bandwidth is 3.4 GHz (14.6–18 GHz). It provides a development direction for future research on flexible absorbing materials.